A novel type of retinoic acid response element in the second intron of the mouse H2Kb gene is activated by the RAR/RXR heterodimer. - Jansa, P (1996)
We have identified and characterized a novel retinoic acid (RA) response element (Hi-RARE) in the second intron of the mouse major histocompatibility H2Kb gene. The Hi-RARE sequence is conserved in all mouse classical and Q class 1 genes, in MHC class 1 genes of the rat, Rhesus macaque, cat and in the vast majority of human classical and non-classical class 1 genes. The Hi-RARE sequence lies within a regulatory element responsible for constitutive expression of a 5' enhancerless H2Kb gene in the Ltk-fibroblasts. Hi-RARE consists of two inverted palindromic RARE consensus sites (5'-PuGGTCA-3') separated by an 8 nt spacer. Mutational analysis revealed that both inverted palindromic hexanucleotide motifs are indispensable functional sites for the 9-cis RA response. The Hi-RARE sequence confers 9-cis RA inducibility to a heterologous promoter. The inducibility is further augmented in embryonal carcinoma cells by the expression of recombinant retinoic acid receptors (PARs) and the retinoid X receptors (RXRs). In vitro, the recombinant RAR/RXR heterodimer creates DNA-protein complex with the Hi-RARE sequence. Treatment of P19 embryonal carcinoma cells with 9C-RA induces the Hi-RARE binding activity of nuclear proteins that proved to be RAR (or RAR-Like)/RXR heterodimer. Thus the Hi-RARE represents a new type of RA response element with a role in the modulation of the expression of MHC class 1 family genes.